AlGaN double-walled nanotubes as ammonia gas sensor - Marana, Naiara L. [UNESP]; Pinhal, Giovanne B. [UNESP]; Casassa, Silvia; Sambrano, Julio R. [UNESP] (My University, 2020)
Nanotubes are one-dimensional material that has been proposed for many different applications, i.e. electronic devices and gas sensor. Due to their reduced size, extended surface area and stability they can represent an alternative to the materials usually applied in gas sensors. In this study, we have carried out Density Functional Theory simulations to explore the possible application of double-walled aluminum and gallium nitride nanotubes as ammonia detectors, as well as of their AlGaN alloys. It was found that ammonia adsorbed preferentially on the external wall on the axial-cation. The adsorption energies, electronic properties, bond critical points and charge transfers showed that the physisorption occurs, and the interaction is particularly intense on the AlN wall. It was also proven that 50% of AlN has the best performance when the external wall is formed by AlN, in terms of stability and interaction with NH3. Therefore, the nanotube alloy with GaN in the internal wall and AlN in the external wall (AloGaiN) showed to be a great candidate for an ammonia sensor.
Keywords: AlGaN; Alloy nanotube; Ammonia; DFT; Gas sensor; Nitride nanotube